2003
DOI: 10.1021/ma034486q
|View full text |Cite
|
Sign up to set email alerts
|

Orientation Distribution Functions Obtained via Polarized Raman Spectroscopy of Poly(ethylene terephthalate) Fibers

Abstract: Polarized Raman microspectroscopy was used to analyze uniaxially oriented fibers of poly-(ethylene terephthalate) (PET). A full analysis of bands at 1616, 998, and 1096 cm -1 is reported for cylindrically symmetric PET fibers. Average orientation and crystal orientation are obtained from the 1616 and 998 cm -1 band, respectively. Although both the 1096 and the 998 cm -1 bands are related to the crystallinity, the second Legendre polynomial of the 1096 cm -1 band, P2,1096, is substantially smaller than for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 27 publications
4
44
0
Order By: Relevance
“…Morphology of polymeric fibers are generally known to affect their macroscopic properties (Yang and Michielsen 2003;Sixta et al 2015;Dawkins 1983). One aspect of morphology is the molecular orientation distribution, typically induced by macroscopic stretching.…”
Section: Introductionmentioning
confidence: 99%
“…Morphology of polymeric fibers are generally known to affect their macroscopic properties (Yang and Michielsen 2003;Sixta et al 2015;Dawkins 1983). One aspect of morphology is the molecular orientation distribution, typically induced by macroscopic stretching.…”
Section: Introductionmentioning
confidence: 99%
“…6,9 This method has the advantage of not requiring any approximation (except uniaxial symmetry), but it is inapplicable for most samples, extremely time-consuming, and subject to large errors due to polarization scrambling and birefringence effects. 6,8 To date, only a few research groups applied this procedure to films and fibers of poly(propylene terephthalate), 6 poly(ethylene terephthalate), 8,10 high-density polyethylene, 7,9 and polystyrene. 11…”
Section: Introductionmentioning
confidence: 99%
“…Polarized Raman microscopy can provide both the second‐order and fourth‐order Legendre polynomials ( P 2 and P 4 , respectively), which describe the orientation, for particular vibrations within samples. Since Bower developed the theory and procedures for determining the orientation of polymer samples by polarized Raman spectroscopy in 1972,1 full analyses of the 1616‐ and 998‐cm −1 bands of PET fiber samples have shown that the former band can provide quantitative orientation information for average chains2 and the latter can provide quantitative crystal orientation 3–5. The 1616‐cm −1 band is the 1,4‐symmetric stretching of the benzene ring,6 and the 998‐cm −1 band is the symmetric stretching of the OCH 2 bond and the stretching of the CC bond in ethylene glycol units in the all‐trans configuration in crystalline PET 7.…”
Section: Introductionmentioning
confidence: 99%
“…The theory for calculating the orientation parameters of fiber symmetry was derived explicitly by Bower1 and summarized by Citra et al8 Yang and Michielsen3, 5 provided a simplified version: where I configurationxy(#) is the scattered intensity in the backscattering (BS) or right‐angle‐scattering (RAS) configuration, with the laser polarization in the x direction and the analyzer polarized in the y direction. The number in parentheses indicates the angle between the long axis of the fiber and the laboratory 3‐axis.…”
Section: Introductionmentioning
confidence: 99%